English Devolution and the Covid‐19 Pandemic: Governing Dilemmas in the Shadow of the Treasury. Issue 2 (8th April 2021) - Warner, Sam; Richards, David; Coyle, Diane; Smith, Martin J.
Abstract: This article explores the question of devolution in the light of the Covid‐19 pandemic's impact on English local government. Criticism of the government's handling of the crisis is widespread and tends to focus on the highly centralised nature of the British state. Here, we attribute the challenges faced by regional and local government in responding to the pandemic primarily to the asymmetric nature of power relations that characterise financial planning and control mechanisms, devised and overseen by the Treasury. We argue that the ongoing crisis underlines the need for a democratic form of devolution—including further fiscal powers for regional and local government—to support the economic recovery. In a context of increasing fiscal uncertainty, the Treasury should seek to unlock the existing powers of local leaders by reforming centralised budgetary constraints and taking accountability and monitoring mechanisms closer to citizens.